2020
DOI: 10.15243/jdmlm.2020.081.2451
|View full text |Cite
|
Sign up to set email alerts
|

Impact of sand mining on the changes of morphological and physical dynamics in Sa’dang River, Pinrang District, Indonesia

Abstract: The research aimed to investigate the morphological changes and physical dynamics conditions of the Sa'dang River associated with river sand mining activities. The research is expected to benefit the efforts of the management of sand mining in this area and enrich knowledge about the issues of river sand mining. The study was conducted in Sa'dang River sand mining area, which includes villages of Pincara, Massewwae and Mangki of Pinrang District in South Sulawesi Province, Indonesia. A field survey was conduct… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 13 publications
0
4
0
Order By: Relevance
“…Table 2 below and Figure 4 lists the identified environmental impacts associated with the sand and gravel mining activities in Maroua. It is clear that sand mining operation can have direct impacts on the environment, causing ecosystem damage and indirect impacts, affecting channel morphology, which in turn affects the distribution of habitats and ecosystem functioning Arsyad et al, 2020;Talukdar and Das, 2020;Rentier and Cammeraat, 2022). This can lead to deterioration in the quality of the riverine environment (Zou et al, 2019;Arsyad et al, 2020;Bhattacharya et al, 2020;Talukdar and Das, 2020).…”
Section: Impacts Of River Sand and Gravel Mining Activities In Study ...mentioning
confidence: 99%
See 1 more Smart Citation
“…Table 2 below and Figure 4 lists the identified environmental impacts associated with the sand and gravel mining activities in Maroua. It is clear that sand mining operation can have direct impacts on the environment, causing ecosystem damage and indirect impacts, affecting channel morphology, which in turn affects the distribution of habitats and ecosystem functioning Arsyad et al, 2020;Talukdar and Das, 2020;Rentier and Cammeraat, 2022). This can lead to deterioration in the quality of the riverine environment (Zou et al, 2019;Arsyad et al, 2020;Bhattacharya et al, 2020;Talukdar and Das, 2020).…”
Section: Impacts Of River Sand and Gravel Mining Activities In Study ...mentioning
confidence: 99%
“…It is clear that sand mining operation can have direct impacts on the environment, causing ecosystem damage and indirect impacts, affecting channel morphology, which in turn affects the distribution of habitats and ecosystem functioning Arsyad et al, 2020;Talukdar and Das, 2020;Rentier and Cammeraat, 2022). This can lead to deterioration in the quality of the riverine environment (Zou et al, 2019;Arsyad et al, 2020;Bhattacharya et al, 2020;Talukdar and Das, 2020). Additionally, many recent researches have shown that stagnant water collects in ponds after sand excavation, creates breeding grounds for mosquitoes and other disease-causing organisms (Shin et al, 2020;Adza et al, 2022;Zou et al, 2019;Rangel-Buitrago et al, 2022;Adza et al, 2022).…”
Section: Impacts Of River Sand and Gravel Mining Activities In Study ...mentioning
confidence: 99%
“…Gold mining plays a substantial economic role and provides sources of employment and income (Wale, 2021) due to the increasing demand for gold (Rukmana, 2020). Despite its economic role, mining activities are associated with deteriorated air quality (Mencho, 2022).…”
Section: Introductionmentioning
confidence: 99%
“…However, this has had adverse effects on the environment, contributing to both water and land pollution in rivers and residential areas due to the leakage of large amounts of waste and heavy metals 1 , and river morphology changes 5 . Notably, riverbank erosion has escalated in recent years, leading to severe property damage and affecting the well-being and security of local communities 6 . Despite these issues, public awareness of the environmental impacts of sand mining remains limited, hindering the implementation of effective mitigation and protection measures.…”
Section: Introductionmentioning
confidence: 99%